2023
DOI: 10.1007/s10637-023-01390-3
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of selective RET inhibitors in RET fusion-positive non-small cell lung cancer: a meta-analysis

Jun-yi Ke,
Shu Huang,
Zhi-tao Jing
et al.

Abstract: Background Rearranged during transfection (RET) fusion-positive occurs in approximately 2% of non-small cell lung cancer (NSCLC). This mutation often predicts metastasis risk and poor prognosis, and current mainstream therapies provide limited patient benefit. Selective RET inhibitors Pralsetinib and Selpercatinib are targeted drugs approved by the US Food and Drug Administration for treating RET-mutated tumors. The phase I/II clinical trial results of their treatment of NSCLC have been published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In our study, the findings associated with the clinical outcomes related to the TTD, TTP, TTNT-D, and ORR favoring selpercatinib versus standard therapies or MKIs also support selpercatinib’s role as the frontline therapy for RET -activated NSCLC and MTC. Evidence from clinical studies and a recent meta-analysis have demonstrated selpercatinib’s safety in patients with RET fusion-positive aNSCLC [ 25 , 26 , 27 ]. In these studies, the occurrence of treatment-related adverse events as well as treatment discontinuation was lower with selpercatinib.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the findings associated with the clinical outcomes related to the TTD, TTP, TTNT-D, and ORR favoring selpercatinib versus standard therapies or MKIs also support selpercatinib’s role as the frontline therapy for RET -activated NSCLC and MTC. Evidence from clinical studies and a recent meta-analysis have demonstrated selpercatinib’s safety in patients with RET fusion-positive aNSCLC [ 25 , 26 , 27 ]. In these studies, the occurrence of treatment-related adverse events as well as treatment discontinuation was lower with selpercatinib.…”
Section: Discussionmentioning
confidence: 99%